PARADIGMA FENOMENOLOGI DALAM STUDI ETIKA AKUNTAN TERHADAP KONSTRUKSI MAKNA DAN PENDEKATAN PENELITIAN - Darwis Said; Arifuddin; Huriyn Putri Askiah Juhari; Inayah Chintaki MZ; Irwan Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Accountant ethics is a fundamental aspect of accounting practice because it is directly related to public trust in the accounting profession. Various cases of financial statement manipulation, abuse of authority, and violations of ethical codes demonstrate that an understanding of ethics cannot be reduced merely to compliance with formal rules. In this context, the phenomenological paradigm offers an alternative perspective for understanding how accountants construct the meaning of ethics based on their lived experiences. This article aims to explain the phenomenological paradigm in the study of accountant ethics by highlighting the construction of meaning, philosophical assumptions, and research approaches employed. The research method discussed is grounded in a qualitative phenomenological approach that seeks to explore accountants’ subjective experiences regarding the ethical dilemmas they encounter. The findings indicate that the meaning of ethics for accountants is shaped through the interaction of personal values, organizational culture, professional pressures, and work experience. The phenomenological paradigm enables researchers to understand ethical reality as a lived experience rather than merely a set of normative rules. Therefore, phenomenology makes an important contribution to enriching the study of accounting ethics by providing a deeper understanding of the consciousness and subjective experiences of accounting professionals.